The use of aprepitant in a case of refractory nausea and vomiting. (July 2014) - Lowery, Lucy; Andrew, Inga; Gill, Sarah; Lee, Mark
Background: This case report describes a patient whose refractory nausea and vomiting significantly improved with the use of aprepitant, a neurokinin receptor antagonist currently only licensed for short-term use in chemotherapy-induced nausea and vomiting. Case presentation: A patient with breast cancer and meningeal metastases had an 18-month history of nausea and vomiting refractory to a number of antiemetics commonly used in palliative care. The nausea and vomiting resolved after receiving two doses of the drug aprepitant. Case management and outcome: Maintenance antiemetic treatment with aprepitant was continued over a 5-month period with no recurrence of nausea and vomiting, and no observed side effects. Conclusions: Aprepitant has a potential role as an antiemetic for refractory symptoms within the palliative-care setting.